Leptospira and Inflammation - C. F. Gonçalves-de-Albuquerque; P. Burth; A. R. Silva; M. Younes-Ibrahim; H. C. Castro-Faria-Neto; M. V. Castro-Faria (Mediators of Inflammation)
Leptospirosis is an important zoonosis and has a worldwide impact on public health. This paper will discuss both the role of immunogenic and pathogenic molecules during leptospirosis infection and possible new targets for immunotherapy against leptospira components. Leptospira, possess a wide variety of mechanisms that allow them to evade the host immune system and cause infection. Many molecules contribute to the ability of Leptospira to adhere, invade, and colonize. The recent sequencing of the Leptospira genome has increased our knowledge about this pathogen. Although the virulence factors, molecular targets, mechanisms of inflammation, and signaling pathways triggered by leptospiral antigens have been studied, some questions are still unanswered. Toll-like receptors (TLRs) are the primary sensors of invading pathogens. TLRs recognize conserved microbial pattern molecules and activate signaling pathways that are pivotal to innate and adaptive immune responses. Recently, a new molecular target has emerged—the Na/K-ATPase—which may contribute to inflammatory and metabolic alteration in this syndrome. Na/K-ATPase is a target for specific fatty acids of host origin and for bacterial components such as the glycolipoprotein fraction (GLP) that may lead to inflammasome activation. We propose that in addition to TLRs, Na/K-ATPase may play a role in the innate response to leptospirosis infection.